Structure and composition of understory vegetation in urban forest of Pekanbaru, Riau Province, Indonesia - DARMAWATI DARMAWATI; LIDIA BELINDA SILITONGA; NURSAL NURSAL; IRDA SAYUTI; IMAM MAHADI; FESKAHARNY ALAMSJAH (Society for Indonesian Biodiversity, 2025)
Abstract. Darmawati, Silitonga LB, Nursal, Sayuti I, Mahadi I, Alamsjah F. 2025. Structure and composition of understory vegetation in urban forest of Pekanbaru, Riau Province, Indonesia. Biodiversitas 26: 4628-4639. Urban forests play a crucial role in maintaining biodiversity; however, human disturbances and the spread of invasive species pose significant challenges to the resilience of understory vegetation. This study examined the structure and composition of understory vegetation in the Pekanbaru Urban Forest in Riau Province, Indonesia and formulated strategies for sustainable management. Research was carried out from June to December 2024 across two canopy conditions Closed Canopy Forest (CCF) and Partial Canopy Forest (PCF) using ten 2×2 m plots in each site (80 m² total). The analyses encompassed species composition, Shannon-Wiener Diversity Index (H?), Evenness Index (E), Dominance Index (D), invasive species proportion, correlation between H? and light intensity, as well as a T-test to compare H? between canopy types. Results revealed that the Poaceae family was the most dominant, with Brachiaria decumbens as the representative species. The T-test showed no significant difference in H? between CCF (2.67) and PCF (2.98), both classified as moderate. Evenness Index values were high (0.89 and 0.87), while dominance values were very low (0.08 and 0.07), indicating a relatively even distribution of species. In total, 38 species were identified, half of which (19 species) were invasive, with a higher abundance recorded in PCF. These findings suggest that canopy mosaics comprising both closed and partially open areas are essential for maintaining understory vegetation in urban forests, as they help support species diversity while limiting invasive dominance. Recommended management strategies include preserving canopy mosaics, controlling invasive species, promoting native species planting, and strengthening conservation policies through active community participation.